Les enjeux de l’intelligence artificielle - Dobnik, Nadja (Scripta manent (Ljubljana), 2024)
In the field of translation didactics, computer-assisted and machine translation tools have long been an integral part of translator training and the assessment of translation competence. The more such translation tools have become developed, the more prominent role they have been assigned not only in professional translation practices, but also in translator training. As a result, assessing the authenticity of students’ translations and their actual translation competence has become increasingly difficult. These issues have become particularly challenging during the Covid-19 pandemic. The advent of generative AI translation tools has resulted in students’ excessive and uncritical reliance on these tools. This paper presents the findings of a case study whose aim was to compare and assess student translations from French into Slovene made without computers with translations generated with the assistance of computers and the full range of functionality that this affords. The results are highly informative and reveal a number of points that merit reflection on the teaching methods in translator training.
Keywords: artificial intelligence; foreign languages; prevodi; translations; tuji jeziki; umetna inteligenca